Strategi Pengembangan Sumber Daya Manusia Untuk Peningkatan Daya Saing Produk UMKM Werken Store - Muhammad Rizki Padli; Vonny Tiara Narundana (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
Werken Store, a micro, small, and medium enterprise (MSME) located in Lampung Province, faces various challenges in enhancing product competitiveness in the digital era, including low employee technical skills, limited digital literacy, and lack of access to formal training. These problems are exacerbated by the absence of a structured training evaluation system and weak collaboration with external institutions. This study aims to analyze the human resource development (HRD) strategies implemented by Werken Store to improve its product competitiveness. A descriptive qualitative approach was used, employing SWOT and EFAS analysis techniques to evaluate internal and external factors affecting HRD. Data were collected through in-depth interviews, participatory observations, document reviews, and supporting literature. The findings show that Werken Store's HRD strategies are dominated by informal, hands-on training (on-the-job training), mentoring by the business owner, and non-financial incentives such as flexible working hours. While these strategies have improved employee motivation and engagement, challenges such as limited digital literacy and the absence of a formal training evaluation system remain. IFAS and EFAS scores of 1.95 and 2.04, respectively, position Werken Store in the “turnaround” strategy quadrant, emphasizing the need for internal improvements. The study concludes that structured, adaptive HRD supported by cross-sector collaboration is key to enhancing MSME product competitiveness. Recommendations include strengthening training evaluation systems, integrating basic digital technologies, and increasing partnerships with educational institutions and government agencies.